Musyawarah Mahasiswa sebagai Model Pengambilan Keputusan dalam Perspektif Sains Sosial dan Islam - Alliya Khairusany; Nayla Raisha Putri; Qintan Riezqy Advi; Tsalisa Nurul Azizah; Edi Seresman (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
Deliberation is a decision-making mechanism commonly used in student organizations, but in practice it is often procedural and tends to lead to majority voting without going through a substantive deliberation process. This article aims to analyze student deliberation practices as a decision-making model from the perspective of modern social sciences and Islamic sciences using a qualitative approach through literature study and normative-comparative analysis reinforced by reflections on student organization practices. The results of the study show that from a social science perspective, student deliberation can be understood through the concepts of deliberative decision-making, participatory leadership, and collective decision-making, which emphasize participation, rational dialogue, and decision legitimacy. Meanwhile, from an Islamic perspective, deliberation (shura) is understood as a moral and spiritual process based on the values of trust, justice, and benefit. Initial findings indicate a gap between the ideal concept of deliberation in Islam and the practice of student deliberation, which is still dominated by group interests and instant voting mechanisms. Therefore, this article concludes that the integration of decision-making theory in social sciences with the values of shura in Islam can form a more deliberative, ethical, and participatory model of student deliberation, which has the potential to improve the quality of decision-making in student organizations while strengthening the character of student leadership based on academic and Islamic values.